2018
DOI: 10.1039/c7ta09134f
|View full text |Cite
|
Sign up to set email alerts
|

A precious metal-free solar water splitting cell with a bifunctional cobalt phosphide electrocatalyst and doubly promoted bismuth vanadate photoanode

Abstract: A bifunctional cobalt phosphide (CoP) electrocatalyst is applied to a doubly promoted BiVO4 photoanode as an oxygen evolution as well as to a cathode as a hydrogen evolution reaction (HER) catalyst to establish a photoelectrochemical (PEC) water splitting cell made of only earth abundant elements without any precious metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…Enlightened from the bifunctional effects of metal phosphide in the field of electrochemistry, some researchers also explored their dual function in PEC water splitting. Kim et al reported a CoP‐coupled Mo:BiVO 4 photoanode connected with CoP‐coupled Ni‐foam synthesized by drop casting, exhibiting excellent PEC‐OER and PEC‐HER activities. And the CoP loading brings ≈90% injection of holes arriving on the surface, which avoided the serious recombination and largely boosted the kinetics of reaction.…”
Section: Cocatalysts For Photoanodes: Construction and Regulationmentioning
confidence: 99%
“…Enlightened from the bifunctional effects of metal phosphide in the field of electrochemistry, some researchers also explored their dual function in PEC water splitting. Kim et al reported a CoP‐coupled Mo:BiVO 4 photoanode connected with CoP‐coupled Ni‐foam synthesized by drop casting, exhibiting excellent PEC‐OER and PEC‐HER activities. And the CoP loading brings ≈90% injection of holes arriving on the surface, which avoided the serious recombination and largely boosted the kinetics of reaction.…”
Section: Cocatalysts For Photoanodes: Construction and Regulationmentioning
confidence: 99%
“…[ 27 ] The binding energies of Co 2p and P 2p lines and Ni 2p and Fe 2p lines are consistent with those previously reported for CoP and FeNi(OH) x . [ 24,25,27 ] The typical elemental peaks of Co, P, Fe, and Ni are also found in the EDS spectra of these co‐catalyst layers (Figure S3, Supporting Information). These results confirm that the CoP and FeNi(OH) x co‐catalysts have been successfully synthesized.…”
Section: Resultsmentioning
confidence: 95%
“…The P 2p core levels (Figure 2e) reveal the presence of phosphide (129.2.0, 130.0 eV) and phosphorus (131.8 and 132.6 eV). [ 25 ] The presence of the phosphorus species has been ascribed to the superficial oxidation of CoP when exposed to air. [ 26 ] Peak fitting analysis for the Ni 2p (Figure 2d) of the as‐deposited FeNi(OH) x co‐catalysts indicates the presence of Ni 2+ (855.3 and 873.1 eV).…”
Section: Resultsmentioning
confidence: 99%
“…first use a CoP catalyst on a BiVO 4 photoanode. [ 140 ] They have found a very similar behavior of BiVO 4 /CoP and BiVO 4 /CoPi in a KPi buffer solution and attribute it to the progressive conversion of CoP particles to a cobalt hydroxyphosphate compound (CoO x –HPO y ) after PEC operation, which is effectively the same phase as CoPi ( Figure 23a ). In comparison, Xia et al.…”
Section: Elements Complements and Combinations Of Oecsmentioning
confidence: 92%
“…Reproduced with permission. [ 140 ] Copyright 2018, The Royal Society of Chemistry. b) J–V curves of bare TiO 2 (black), Co 3 O 4 /TiO 2 (red), O‐Ar/Co 3 O 4 /TiO 2 (green), and Ar‐Co 3 O 4 /TiO 2 (blue) photoanodes.…”
Section: Elements Complements and Combinations Of Oecsmentioning
confidence: 99%